Exercise stress echocardiography of the right ventricle and pulmonary circulation - Gargani, Luna; Pugliese, Nicola Riccardo; De Biase, Nicolò; Mazzola, Matteo; Agoston, Gergely; Arcopinto, Michele; Argiento, Paola; Armstrong, William F.; Bandera, Francesco; Cademartiri, Filippo; Carbone, Andreina; Castaldo, Rossana; et al. (Journal of the American College of Cardiology, 2023)
Background - Exercise echocardiography is used for assessment of pulmonary circulation and right ventricular function, but limits of normal and disease-specific changes remain insufficiently established. - Objectives - The objective of this study was to explore the physiological vs pathologic response of the right ventricle and pulmonary circulation to exercise. - Methods - A total of 2,228 subjects were enrolled: 375 healthy controls, 40 athletes, 516 patients with cardiovascular risk factors, 17 with pulmonary arterial hypertension, 872 with connective tissue diseases without overt pulmonary hypertension, 113 with left-sided heart disease, 30 with lung disease, and 265 with chronic exposure to high altitude. All subjects underwent resting and exercise echocardiography on a semirecumbent cycle ergometer. All-cause mortality was recorded at follow-up. - Results - The 5th and 95th percentile of the mean pulmonary artery pressure-cardiac output relationships were 0.2 to 3.5 mm Hg.min/L in healthy subjects without cardiovascular risk factors, and were increased in all patient categories and in high altitude residents. The 5th and 95th percentile of the tricuspid annular plane systolic excursion to systolic pulmonary artery pressure ratio at rest were 0.7 to 2.0 mm/mm Hg at rest and 0.5 to 1.5 mm/mm Hg at peak exercise, and were decreased at rest and exercise in all disease categories and in high-altitude residents. An increased all-cause mortality was predicted by a resting tricuspid annular plane systolic excursion to systolic pulmonary artery pressure <0.7 mm/mm Hg and mean pulmonary artery pressure-cardiac output >5 mm Hg.min/L. - Conclusions - Exercise echocardiography of the pulmonary circulation and the right ventricle discloses prognostically relevant differences between healthy subjects, athletes, high-altitude residents, and patients with various cardio-respiratory conditions. (Right Heart International NETwork During Exercise in Different Clinical Conditions; NCT03041337)
Online verfügbar 13 November 2023, Version des Artikels 13 November 2023
Gesehen am 15.04.2024